Domain name suspension in Russia – Internet-infrastructure-based tool to control free expression - Sivetc Liudmila (Helsingin yliopisto, 2025)
This article focuses on the state control of the Russian Internet infrastructure. Since 2012, Russian State has tightened control over the Russian Internet. According to some researchers, Russia set as a goal the achievement of total control over any online activity. As regards online free expression, Russia introduced extensive legislation to intensify state control, a decision that has been criticized as “legal haste,” “blitzkrieg,” and “the occupation of Runet.” The indirect regulation by infrastructure has direct effects on online speech because it can be expressed and accessed only through the Internet infrastructure.
Viestin viemää – Viestintäoikeuden vuosikirja 2021